Clinical significance of parathyroid hormone in mineral and glucose metabolism disorders among patients with primary aldosteronism - Zhilian Sun; Wenxiu Liu (SAGE Open Medicine)
Objective: To investigate the differences in mineral and glucose metabolic disorders among patients with primary aldosteronism, nonfunctional adrenal tumors, and controls. Methods: A retrospective analysis was conducted on clinical data from 578 patients, including those with primary aldosteronism, nonfunctional adrenal tumors, and control subjects, at our hospital between January 2013 and December 2023. Biochemical indices including parathyroid hormone, serum potassium, serum calcium, urine potassium, urine calcium, plasma renin, plasma aldosterone, glycosylated hemoglobin, insulin resistance index, and pancreatic beta cell function index were compared among the three groups. Results: Compared with the nonfunctional adrenal tumors and control groups, primary aldosteronism patients exhibited significantly higher levels of parathyroid hormone, urinary potassium, and aldosterone ( p  < 0.05), while their serum potassium and serum calcium levels were significantly lower ( p  < 0.05). Additionally, primary aldosteronism patients had higher glycosylated hemoglobin levels, lower HOMA-IR, and lower HOMA-β levels ( p  < 0.05). Pearson’s correlation analysis revealed that serum parathyroid hormone levels were negatively correlated with serum potassium, serum calcium, serum renin activity, and HOMA-β levels, while positively correlated with urinary potassium, urine calcium, blood carbon dioxide combining power, urine pH, serum aldosterone, and HOMA-IR levels. Stepwise regression analysis indicated that HOMA-IR and aldosterone were the main factors influencing parathyroid hormone levels. Based on receiver operating characteristic curve analysis, the optimal cut-off value for parathyroid hormone in diagnosing primary aldosteronism was 62.1 pg/ml, with a sensitivity of 94.4% and specificity of 81.0%. Conclusion: Primary aldosteronism is often characterized by elevated parathyroid hormone levels, which can exert direct adverse effects on mineral and glucose metabolism. Elevated parathyroid hormone levels serve as a valuable indicator in the screening of primary aldosteronism.